2022
DOI: 10.1177/18632521221106376
|View full text |Cite
|
Sign up to set email alerts
|

Children treated for developmental dysplasia of the hip at birth and with normal acetabular index at 1 year: How many had residual dysplasia at 5 years?

Abstract: Purpose: The purpose of the study was to assess the effect of further follow-up for children treated for developmental dysplasia of the hip, with normal clinical and radiological findings at 1-year time point. The effect was quantified by the number of hips with a pathologic deterioration up to 5 years. Methods: Among 47,289 children born in Sør-Trøndelag county in Norway between 2003 and 2015, 265 children had developmental dysplasia of the hip. Of these, 164 children (239 hips) treated for developmental dysp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 36 publications
2
7
0
Order By: Relevance
“…Of their cohort, 30% with residual dysplasia subsequently went on to have secondary procedures to correct the acetabular dysplasia. 20 This is in line with our observations with 3/14 (21%) of our cohort with residual dysplasia requiring pelvic osteotomies.…”
Section: Figuresupporting
confidence: 93%
See 1 more Smart Citation
“…Of their cohort, 30% with residual dysplasia subsequently went on to have secondary procedures to correct the acetabular dysplasia. 20 This is in line with our observations with 3/14 (21%) of our cohort with residual dysplasia requiring pelvic osteotomies.…”
Section: Figuresupporting
confidence: 93%
“…19 However, previous authors have reported the incidence of RAD at longer follow-ups between 3% and 26% despite successful early PH treatment. 1,[8][9][10][11][12]20 These studies unfortunately all used varied definitions of RAD.…”
Section: Figurementioning
confidence: 99%
“…Staying on the theme of developmental dysplasia of the hip (DDH), this paper from Trondheim (Norway) asked yet another pertinent and unanswered question. 6 The authors set out to establish what the residual dysplasia rates are at five years of age in those patients treated for DDH at birth, and in whom a normal acetabular index (AI) was achieved at one year. The reason for the interest in this question was the introduction of a selective ultrasound screening service, which included a final examination at age five years, but the team wished to examine if follow-up could be safely ended at age one year, with benefits for healthcare providers and patients alike.…”
Section: Children Treated For Developmental Dysplasia Of the Hip At B...mentioning
confidence: 99%
“…A noteworthy fact is that in communities where mothers carry their neonates on their backs with the hips abducted have a lower incidence of DDH. 4,5 Regardless of the factors, it is extremely important to detect DDH as early as possible. By early detection of the condition, non-invasive management options such as the Pavlik Harness may be used.…”
Section: Introductionmentioning
confidence: 99%
“…It is not unusual for radiographs to be ordered in newborns and infants less than six months of age for assessment of DDH. 4 There is a lack of literature to outline prevalent practices for radiological screening and diagnosis of DDH in our country.…”
Section: Introductionmentioning
confidence: 99%